Benefit of adjunct universal rectal screening for Chlamydia genital infections in women attending Canadian sexually transmitted infection clinics. (November 2017) - Thanh, Nguyen X; Akpinar, Ilke; Gratrix, Jennifer; Plitt, Sabrina; Smyczek, Petra; Read, Ron; Jacobs, Philip; Wong, Tom; Singh, Ameeta E
Adding universal rectal screening to urogenital screening should positively impact rectal Chlamydia trachomatis (CT) incidence in affected populations. A dynamic Markov model was used to evaluate costs and outcomes of three rectal CT screening strategies among women attending sexually transmitted infection clinics in Alberta, Canada: universal urogenital-only screening (UG-only), additional selected (exposure-based) rectal screening (UG+SR), and additional universal rectal screening (UG+UR). The model included two mutually exclusive health states: infected and susceptible. Additionally, the model included two rounds of transmission: male sex partners of women infected with rectal-only CT and female sex partners of those men. CT complications impacting patients' quality of life (QALY) were considered. Alberta and Canadian data were used to estimate model inputs. We used a health care perspective, a time period of 10 years, and a discount rate of 3% for analyses. Compared to UG-only screening, the incremental cost effectiveness ratios (ICERs) were CA$34, 000 and CA$49, 000 per QALY gained for UG+SR and UG+UR screening strategies, respectively. Compared to UG+SR, the ICER was CA$62, 000 per QALY gained for the UG+UR strategy. Both adjunct selected and universal rectal screening strategies are cost effective compared to UG-only screening, and UG+UR screening is cost effective when compared to UG+SR screening.